(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Globally, human metapneumovirus (hMPV) constitutes a more significant proportion of acute respiratory tract infections (ARTIs), which are a primary cause of morbidity and mortality in children. A range of viruses, such as influenza viruses, respiratory syncytial virus (RSV), picornaviruses, coronaviruses, parainfluenza viruses, and adenoviruses, have been linked to various respiratory syndromes across all age categories. Notably, some of these viruses circulate and co-infect individuals, increasing the possibility of resulting in complex interactions that may affect disease severity, immune response, and epidemiology. It is also known that the majority of children contract hMPV by the age of 5, with the most severe cases found in infants, comprising both symptomatic and asymptomatic infections. Although hMPV is widely common, there are currently no approved vaccines or specific antiviral therapies available, highlighting the need for more research into focused treatments and vaccine development. Improvements in molecular diagnostics have increased detection rates, though difficulties persist in disease monitoring and management. The 2024-2025 current outbreak in China commenced in December 2024 and has experienced a rapid rise in cases, especially among children aged 14 and younger. Additionally, other countries like the United Kingdom (UK), France, and Germany have reported cases of the virus, reflecting its extensive spread. Consequently, an understanding of the epidemiology of hMPV is essential for creating effective targeted interventions. This review provides a global perspective of hMPV and points out knowledge gaps to drive future research initiatives in its management, prevention, and control